218 Management strategies for neuroimmunological complications following treatment with immune checkpoint inhibitors. Issue 12 (14th November 2019) - Bose, Smriti; Sumangala, Salini; Steven, Neil; Jacob, Saiju
Abstract : Objective: The use of immune checkpoint inhibitors (CIs) for malignancies has revolutionised oncological management in the last few years. These agents are known to cause immune-mediated complications in various systemic organs. The neurological complications of these are now being increasingly recognised. The cases managed in our institution where there were neuroimmunological complications following CIs were reviewed. We discuss management strategies for early recognition and treatment, thus minimising morbidity. Method: A joint effort by neurologists and medical oncologists to review clinical practice guidelines for management of neurological adverse effects of checkpoint inhibitors. This was based on a review of several cases reported, as well as experience from all the cases managed in our hospital. Results: There are no British guidelines from the neurological perspective for early identification of symptoms. Guidelines are based on expert consensus and also on treatments reviewed from literature. Conclusion: Recommendations advice early identification of signs and symptoms followed by grading them as mild, moderate and severe (grades 1, 2, 3). Grade 1 symptoms require continuation of the CIs and symptomatic management. CIs should be stopped temporarily for grade 2 and permanently for grade 3 symptoms. Steroids plasma exchange, IVIg would be the first line of treatment.